EDUKASI PENDAMPINGAN STUDI NASKAH FILOLOGI KE MUSEUM SIGINJEI JAMBI - Zahar, Erlina; Rahima, Ade; Tara, Firman; Sujoko, Sujoko (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The purpose of this Community Service is to develop philology lecture materials for PBSI students and guide students in conducting philology manuscript studies at the Siginjei Jambi Museum. The Service Learning method of this community service uses socialization in the form of lectures, providing materials, and field studies. The Service Learning method is carried out because of the nature of serving the community through a community or several people who aim to develop themselves. The number of students in this activity is 21. The results of this Community Service are data to be written into the PKM report, which is the main task of lecturers in the Tri Dharma of higher education and to add to the teaching materials used in learning philology courses. The conclusion is that this assistance aims to develop philology lecture materials for students, where materials related to philology, namely manuscripts/handscripts, can be actualized through this visit.